A metal-organic cage incorporating multiple light harvesting and catalytic centres for photochemical hydrogen production - Sha Chen (Nature Portfolio, 2016)
Photocatalytic water splitting is a promising route to hydrogen generation from renewable solar power. Here, the authors report a hydrogen-evolving photochemical molecular device based on a self-assembled coordination cage, which simultaneously incorporates multiple photosensitizing and catalytic metal centres.